Acetylcholine Inhibits Tumor Necrosis Factor α Activated Endoplasmic Reticulum Apoptotic Pathway via EGFR‐PI3K Signaling in Cardiomyocytes. Issue 4 (April 2015) - Miao, Yi; Bi, Xue‐Yuan; Zhao, Mei; Jiang, Hong‐Ke; Liu, Jin‐Jun; Li, Dong‐Ling; Yu, Xiao‐Jiang; Yang, Yong‐Hua; Huang, Ning; Zang, Wei‐Jin
<x xml:space="preserve">Abstract</x> Previous findings have shown that acetylcholine (ACh) decreased hypoxia‐induced tumor necrosis factor alpha (TNF α) production, thus protected against cardiomyocyte injury. However, whether and how ACh affects TNF α‐induced endoplasmic reticulum (ER) stress and cell apoptosis remain poorly defined. This study was aimed at determining the effect of ACh in H9c2 cells after TNF α stimulation. Presence of ER stress was verified using the ER stress protein markers glucose regulatory protein 78 (GRP78) and C/EBP homologous protein (CHOP). Cell apoptosis was shown by caspase‐3 activation and terminal deoxynucleotidyl transferase mediated dUTP‐biotin nick end labeling. Exogenously administered ACh significantly decreased these TNF α‐induced changes. Moreover, when the cells were exposed to nonspecific muscarinic receptor (M AChR) inhibitor atropine, methoctramine (M2 AChR inhibitor) or the epidermal growth factor receptor (EGFR) inhibitor AG1478, the cardioprotection elicited by ACh was diminished. Furthermore, the above effects were also blocked by M2 AChR or EGFR siRNA, indicating that EGFR transactivation by M2 AChR may be the major pathway responsible for the benefits of ACh. In addition, LY294002, a phosphatidylinositol‐3‐kinase (PI3K) inhibitor, displayed the similar trends as AG1478, suggesting that PI3K/Akt signaling may be the downstream of EGFR in ACh‐elicited anti‐apoptotic property. Together, these data indicate that EGFR‐PI3K/Akt signaling is involved in M2 AChR‐mediated ER apoptotic pathway suppression and the subsequent survival of H9c2 cardiomyocytes. We have identified a novel pathway underlying the cardioprotection afforded by ACh. J. Cell. Physiol. 230: 767–774, 2015. © 2014 Wiley Periodicals, Inc.